A dimensão afetiva e sua relevância no processo de ensino-aprendizagem: uma abordagem sociocognitiva - Silva, Márcia Lustosa; Cruz, Valmira Amariz; Silva, Frederico Fonseca (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper aims to investigate the importance of affectivity in the teaching-learning process. Based on the learning theories of Piaget and Vygotsky who conceive as the intrinsic relationship between the cognitive and affective processes in human psychic functioning. The methodology undertaken was qualitative seen that 48 high school students from a Technical School, a full scheme of the State of Pernambuco (Brazil) were evaluated. The instruments used were the Affect-Performance Diagram adapted analysis, developed by Silva and Teixeira (2008). The results indicate the affective aspect, as well as the relationship between teacher and student, as key variables to determine the process of teaching and learning.